Design of the Gear Reducer Mechanism with Double Motor Redundancy Drive of the Refueling Switch - Maolin Tan; Lingling Zhao; Jing Wei (Jixie chuandong)
The design and analysis of the refueling switch gear reducer mechanism are carried out. Within the design conditions and design requirements comprehensively considered, the modeling,statics analysis and acceleration impact dynamic load simulation analysis are carried out.The results show that the designed gear reducer meets the design requirements and design conditions,and the maximum strain,maximum deformation and maximum instantaneous impact stress are less than the allowable value.Besides, the accuracy of the finite element model is verified by the real object, and all functions could be realized through the test without interference,which fully meet the design requirements.